Prevalence and risk factors for infection of Neospora caninum in sheep from Lages county, Santa Catarina State, Brazil (Revista de Ciências Agroveterinárias, 2011)
Neosporosis is a protozoal disease caused by Neospora caninum. Dogs, coyotes and dingoes are definitive hosts and among livestock, the sheep is one of the intermediate hosts, which may have mainly reproductive problems, and hence significant economic losses. Aiming to determine the prevalence of N. caninum infection in sheep in Lages county, Santa Catarina State; identify possible risk factors for infection in sheep; and correlate the prevalence of N. caninum antibodies with risk factors assessed, blood was collected from 360 sheep on 13 farms. The detection of IgG antibodies was performed by indirect fluorescent antibody test (IFAT). Sera were initially tested at 1:50 dilution and those positive were retested in serial dilutions of two basis until the maximum degree reactive. Information about the age, sex, race, animal category, breeding system, diet, water source, contact with dogs and reproductive disorders were obtained through the application of a questionnaire to the owners. The data were statistically analyzed using Fisher’s exact and chi-square tests (p≤0.05). In 46.15% (6/13) of the farms, at least one positive animal was identified. The variation range of percentage of positive animals among properties ranged from zero to 25.81%. Positive reactions with titers ≥ 50 were found in 21 sheep (5.83%). The titers found ranged from 50 to 400, and five animals (23.81%) had a titer of 50; fi ve (23.81%) at 100; six (28.57%) at 200 and fi ve animals (23.81%) had a titer of 400. There was no association between positivity to N. caninum in sheep and the variables analyzed. The results indicate that N. caninum is present in significant percentages in sheep from Lages County, Santa Catarina State, Brazil.
Keywords: Neospora caninum; Sheep; IFAT; Reproductive problems.